Russia’s Economic Development Situation and Its Influence on Sino-Russian Economic and Trade Cooperation - Jiang, Ziwen (International Journal of Global Economics and Management, 2024)
This paper aims to analyze the development of the Russian economy and explore its impact on Sino-Russian economic and trade cooperation. Firstly, the paper reviews the historical background and current situation of the Russian economy, with a focus on analyzing the main economic indicators and government policies. Secondly, the historical background, current situation, and cooperation areas of Sino-Russian economic and trade cooperation are summarized, and the opportunities and challenges of cooperation are discussed. Subsequently, the paper analyzes the factors influencing the impact of Russian economic development on Sino-Russian economic and trade cooperation and prospects for future cooperation. Finally, based on the research results, strategies and suggestions for promoting the development of Sino-Russian economic and trade cooperation are proposed to provide reference and support for bilateral cooperation.